Identificación de estreptococo b-hemolítico en hisopados nasofaríngeos de perros con patologías respiratorias en diferentes clínicas en la ciudad de Machala - Pineda Flores, Jeniffer Virginia (2017)
Respiratory pathologies in canines have been one of the main diseases presented in the daily clinic. In the cold season we have the visits of the owners of the pets with the presence of cough, difficulty in breathing by the congestion of the respiratory mucous membranes, tearing, excessive humidity and presence of secretion in the nostrils. All this set of clinical signs leads to the presence of respiratory diseases, complicating the health status of the animal mainly in puppies and geriatric dogs. Infectious diseases include viruses, fungi, mycoplasmas and bacteria. Among the bacterial diseases, β-hemolytic streptococci have been identified as one of the causative agents, which can be found as a natural inhabitant of the upper respiratory tract, such as the nasopharynx. These types of bacteria are classified by Lancefield in serological groups A, B, C, D, F, and G by the degree of haemolysis they cause at the time of culture in media such as lamb's blood agar. Within the β-hemolytic identified in the dogs is the group G Streptococcus canis, isolated from oral and vaginal microbiota in canines, which can become opportunistic pathogens according to the health condition of the animal. Streptococcus equi with its subspecies Streptococcus zoopidemicus as well as Streptococcus dysgalactiae with its two subspecies: equisimilis and dysgalactiae belonging to the C group of Lancefield. The general objective of this work was to identify the presence of β-hemolytic streptococcus in nasopharyngeal discharges from dogs and to study antimicrobial susceptibility-related findings with the occurrence of respiratory diseases. Twenty-five dogs (Mestizos, Great Danes, French Poodle, Pequines, Chihuahua, Labrador, Miniature Doberman, Pitbull, and Shitzut) were used, from one month and a half to 16 years old, of different breeds and with clinical signs of respiratory diseases, in three different clinics of the City of Machala. The sample was taken with a swab at the level of the pharyngeal entrance and in the nostrils. For the bacterial identification, the macroscopic study was carried out observing the shape, size and aspects of the colonies as well as the production of hemolysis. Subsequently, the staining of Gram and the microscopic study of the bacterium were performed. Of the 25 dogs that were examined at the three Machala clinics, the predominant isolation was the Staphylococcus spp bacteria that were identified as positive cocci and catalase positive, β-hemolytic streptococci, occupying the second place. The genera Escherichia, Proteus, Enterococcus and Klebsiella were found in a lower percentage and were also isolated in a lower percentage of non-fermenting Gram negative bacilli (BGNNF). Serological agglutination test in Latex (Streptex) was performed resulting in three positive samples from the Lancefield G serological group to which belongs to Streptococcus canis and one positive from the Lancefield serotype D to which Enterococcus belongs. In the antimicrobial susceptibility test it was observed that Streptococcus canis is sensitive to penicillin and erythromycin and presented intermediate sensitivity to tetracycline. In conclusion, it can be said that β-hemolytic streptococci are found in the pharynx of dogs and could be the direct and indirect cause of respiratory diseases of canines. It is recommended to carry out more bacterial isolates in dogs with respiratory diseases as well as antimicrobial susceptibility in order to carry out adequate treatment and to avoid bacterial resistance.